The recent political situation in Ethiopia and rapprochement with Eritrea - Amsalu K. Addis; Simplice Asongu; Zuping Zhu; Hailu Kendie Addis; Eshetu Shifaw (African Governance and Development Institute (AGDI), 2020)
The aim of this article is designed to provide an overview of the historical and contemporary relations between Ethiopia and Eritrea as well as to examine the recent geopolitical situation and the perception of local people in Ethiopia. This paper is mainly based on secondary data analysis of the available secondary information and news reports, online articles, academic literature, interviews and discussions. The war between Ethiopia and Eritrea brought political, economic and social security threats to the Horn of Africa. Although the economy in Ethiopia is at the developing stage, recent protests have shaken the country to its core. Since 2015, anti-government protests have been triggered over freedom of the press, land rights, underrepresented seats in the coalition parties, and horizontal inequality in economic, political and social affairs among ethnic groups across the country. In this study, it is established that the unrestrained political circumstance of the current regime has created dissension and violence among the public, and thus led to escalating political, economic and security crises in the country. If this issue is not rectified quickly, the peace in the country may be jeopardised. Another issue is that although Ethiopia-Eritrea rapprochement is appreciated, the agreement between the two leaders and their foreign policy orientation is still unclear.
Keywords: 330; Ethiopia; Eritrea; Protest; Amhara; Oromo; State of emergency; EPRDF